Effect of welding layers and interlayer temperature on welding residual stress and deformation of Q345/316L dissimilar steel - Yongyou Zhu; Jianneng Zheng; Houbin Li; Yuping Liu; Bensheng Huang; Tianning Li; Peng Tang (Materials Research Express)
Dissimilar steel welding is widely used in machinery, chemical industry, electric power and other fields. Due to the different welding materials, the distribution of residual stress and deformation of welded joints is complex. In order to study the influencing factors and variation rules of residual stress and deformation distribution of dissimilar steel joints, considering the nonlinear physical and mechanical properties of welding materials and the latent heat of phase change during welding, based on the SYSWELD platform, taking Q345 carbon steel and 316L stainless steel as the research objects, the double ellipsoid heat source model was used to study the effects of welding layers and interlayer temperature on the residual stress and deformation of joints. The results show that the increase of the number of welding layers is beneficial to expand the distribution of residual stress, and has no obvious effect on the residual stress of the weld, but it will reduce the residual stress of the base metal near the weld. However, the increase of the number of layers will also aggravate the deformation of the weld. Therefore, it is necessary to consider the design of the number of welding layers considering the thickness of the component. At the same time, the study also found that the interlayer temperature has a certain influence on the residual stress and deformation of the joint. The increase of the interlayer temperature will reduce the welding angle deformation, and has little effect on the transverse shrinkage and the residual stress of the joint. Therefore, a lower interlayer temperature should be selected for multi-layer and multi-pass welding of dissimilar steel to ensure the quality of the welded joint.